Understanding asymmetrical malpigmentation in flatfishes and improvement measures for aquaculture - Bo Zhang; Changwei Shao; Songlin Chen; Baolong Bao (John Wiley & Sons Australia. Ltd, 2025)
Pleuronectiformes, an order known as flatfishes, is important in mariculture worldwide with the unique characteristic of body asymmetry, and thus has value in scientific research. Also, as an economically important species, flatfishes have great developing potential for industrial aquaculture. Their rapid growth, rich nutrition, delicious taste, and high-quality protein are accepted and favoured by consumers all over the world. Due to large-scale breeding and expanding production, however, different degrees of abnormal body colour flatfishes have emerged, which seriously affect commercial value of the fish, even reducing it by half; therefore, relevant research has been carried out. This article reviews how environmental factors affect body colour abnormalities and possible genetic mechanism of abnormal body colouration of flatfishes, summarizes the hypotheses of the mechanism of body colour asymmetry, and proposes the latest improvement measures obtained at the genomic screening level to prevent the occurrence of abnormal body colour. This review suggests the molecular mechanism of abnormal asymmetric distribution of body colour, suggests measures for avoiding malpigmentation in flatfishes, and provides a constructive theoretical reference for healthy development of the flatfish breeding industry.